Physics and applications of metallic magnetic calorimeters - Kempf, Sebastian; Fleischmann, Andreas; Gastaldo, Loredana; Enss, Christian (Journal of low temperature physics, 2018)
Metallic magnetic calorimeters (MMCs) are calorimetric low-temperature particle detectors that are currently strongly advancing the state of the art in energy-dispersive single particle detection. They are typically operated at temperatures below 100mK100mK100\,mK and make use of a metallic, paramagnetic temperature sensor to transduce the temperature rise of the detector upon the absorption of an energetic particle into a change of magnetic flux which is sensed by a superconducting quantum interference device. This outstanding interplay between a high-sensitivity thermometer and a near quantum-limited amplifier results in a very fast signal rise time, an excellent energy resolution, a large dynamic range, a quantum efficiency close to 100% as well as an almost ideal linear detector response. For this reason, a growing number of groups located all over the world is developing MMC arrays of various sizes which are routinely used in a variety of applications. Within this paper, we briefly review the state of the art of metallic magnetic calorimeters. This includes a discussion of the detection principle, sensor materials and detector geometries, readout concepts, the structure of modern detectors as well as the state-of-the-art detector performance.